Sosialisasi Eksistensi Generasi Muda Terhadap Penggunaan Bahasa Indonesia Di SMK Negeri 6 Padang - Najmi Hayati; Dwi Mutia Chan; Zuraida Chairani; Susanti Marisya; Novi Fitriani; Relita (Kilau Publishing, 2025)
This community service activity aims to raise students’ awareness and pride in using proper and correct Indonesian amid the challenges of globalization and popular culture. The activity was carried out in three stages: planning, implementation (material delivery and simulation), and evaluation. The results show that students often mix Indonesian with foreign languages and slang. This outreach successfully motivated students to use Indonesian more actively in appropriate communication contexts. The activity is expected to promote the preservation of the Indonesian language as a national identity.